1936
DOI: 10.1084/jem.63.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Etiology of Rabbit Pox

Abstract: The preceding paper contains the results of various reinoculation experiments in which the viruses of rabbit pox, virus I I I disease, infectious m y x o m a of rabbits, culture (dermo) vaccinia, and neurovaccinia were compared (1). The findings with respect to the reaction of recovered rabbits to exposure to clinical cases of pox, together with the observations on a calf inoculated with pox, two specimens of vaccine virus, and neurovaccine were also reported. The present paper is concerned with the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1936
1936
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Furthermore, the serum of pox recovered rabbits completely neutralized pox virus (4). The results of crossed inoculation and immune serum-virus neutralization experiments showed that there was no specific relationship between the viruses of pox and virus III disease (3,4). A similar conclusion was drawn from the experiments on pox and infectious myxoma of rabbits (3).…”
Section: G E N E R a L Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Furthermore, the serum of pox recovered rabbits completely neutralized pox virus (4). The results of crossed inoculation and immune serum-virus neutralization experiments showed that there was no specific relationship between the viruses of pox and virus III disease (3,4). A similar conclusion was drawn from the experiments on pox and infectious myxoma of rabbits (3).…”
Section: G E N E R a L Discussionmentioning
confidence: 67%
“…Rabbits which had recovered from the spontaneous or the experimental disease were refractory to inoculation of pox virus, nor did clinical manifestations of the infection develop under conditions of exposure to florid cases (3). Furthermore, the serum of pox recovered rabbits completely neutralized pox virus (4). The results of crossed inoculation and immune serum-virus neutralization experiments showed that there was no specific relationship between the viruses of pox and virus III disease (3,4).…”
Section: G E N E R a L Discussionmentioning
confidence: 99%
See 2 more Smart Citations